The Pen-Picture of Modern Broken Loveless Society in Maugham’s The Kite (London Journal of Research In Humanities and Social Sciences, 2025)
William Somerset Maugham portraits an awesome family picture in ‘The Kite’. In  this short story the interesting matter is the relationship among family members. A simple  story exposes the complexities of human psychology in a lucid and catchy way. In remote  past Maugham scattered the seed of separation which brings the theme of divorce in our  modern loveless society. N ow divorce is every classes’ cup of tea in our society. Smashing the  kite indicates smashing the lovely conjugal relationship in our modern society. This paper  attempts to entrap the word picture of modern society in the short story ‘The Kite’ which  was written in 1947.
Keywords: inclusive education; teacher training.; Quantitative analysis; Deafness; Social Design; Precarity; Graphics; Local Print Shops; human; nature; theology; Divine; Christ; Mnolahma Nelca effect; Ice Wall; Anthropological ritual; Mythological origins; conflict; Ghana.; festival; artistic; expression; celebration; resolution; family; temperament; loneliness; traditional; emotional; interactions; Relationship; Psychology; Modern; kite; complex